2013
DOI: 10.1134/s002136401222002x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the flux of primary cosmic ray antiprotons with energies of 60 MeV to 350 GeV in the PAMELA experiment

Abstract: It is interesting to measure the antiproton galactic component in cosmic rays in order to study the mechanisms by which particles and antiparticles are generated and propagate in the Galaxy and to search for new sources of, e.g., annihilation or decay of dark matter hypothetical particles. The antiproton spectrum and the ratio of the fluxes of primary cosmic ray antiprotons to protons with energies of 60 MeV to 350 GeV found from the data obtained from June 2006 to January 2010 in the PAMELA experiment are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 23 publications
3
119
0
Order By: Relevance
“…For a WIMP mass m χ of 1 TeV, the positron production rate needs to be enhanced by a factor of a thousand to match the measurements. The second difficulty lies in the absence, up to 100 GeV, of a similar excess in the antiprotons, since the PAMELA measurements of the antiprotonto-proton ratio (Adriani et al 2009a) and of the absolute flux (Adriani et al 2010(Adriani et al , 2013b are consistent with the expected astrophysical background of secondary species. DM particles cannot couple with quarks under the penalty of overproducing antiprotons as shown by Cirelli et al (2009b) and confirmed by Donato et al (2009).…”
Section: Introductionmentioning
confidence: 89%
“…For a WIMP mass m χ of 1 TeV, the positron production rate needs to be enhanced by a factor of a thousand to match the measurements. The second difficulty lies in the absence, up to 100 GeV, of a similar excess in the antiprotons, since the PAMELA measurements of the antiprotonto-proton ratio (Adriani et al 2009a) and of the absolute flux (Adriani et al 2010(Adriani et al , 2013b are consistent with the expected astrophysical background of secondary species. DM particles cannot couple with quarks under the penalty of overproducing antiprotons as shown by Cirelli et al (2009b) and confirmed by Donato et al (2009).…”
Section: Introductionmentioning
confidence: 89%
“…More recently, measurements of the cosmic ray antiproton spectrum by PAMELA [10][11][12] (and in the near future, by AMS-02) have reached the level of precision required to probe thermal dark matter particle candidates with masses in the range of ∼10-100 GeV [13][14][15][16][17][18][19][20][21][22], yielding constraints that can be comparably stringent to those derived from gamma-ray telescopes [23,24]. Such constraints are, however, subject to large astrophysical uncertainties associated with the propagation of cosmic rays through the Milky Way.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we revisit the cosmic ray antiproton spectrum, as measured by the PAMELA experiment [10][11][12], and consider the implications for annihilating dark matter. To this end, we make use of a large set of propagation models, with parameters fit to the observed spectra of boron, carbon, beryllium, and other cosmic ray nuclei (as identified and evaluated in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For a dark matter mass larger than a few GeV, the flux of antiprotons features a cut off at the dark matter mass. The most accurate measurements of thep flux at the Earth was reported by the space-borne detectors PAMELA [44] and AMS-02 [45]. The discovery of an excess around 100 GeV was recently claimed [46,47].…”
Section: Jhep11(2017)132mentioning
confidence: 99%
“…We derived constraints on the dark matter annihilation cross section σv from the cosmic ray antiproton flux measured by PAMELA [44] as well as AMS-02 [45], following the procedure described in [75]. Secondary antiprotons constitute the astrophysical background.…”
Section: Indirect Detectionmentioning
confidence: 99%